Barmhjertig og ubekymret. Om Jesus-billedet hos den tidlige Løgstrup - Møller, Maria Louise Odgaard (Dansk Teologisk Tidsskrift, 2009)
The aim of this article is to characterise the understanding of the Jesus figure in two of K.E. Løgstrup’s (1905-81) early works: the doctoral dissertation, Den erkendelsesteoretiske konflikt mellem den transcendentalfilosofiske idealisme og teologien, and a small book on the relation between the sermon and its text, Prædikenen og dens tekst, both from the 1940s. None of the works focus on the Jesus figure per se. However, it is possible to outline Løgstrup’s understanding of Jesus based on the two works, since an interpretation of Jesus’ life and work is important for Løgstrup in order to support his perception of the Jewish-Christian understanding of life in its contrast to what he calls a profane understanding. Løgstrup’s picture of Jesus is controversial compared to traditional Christological notions, since it concentrates solely on his life and work, while not referring to his death and resurrection. This can partly be explained by the polemic context in which Løgstrup’s discussions of Jesus appear, namely his critique of the profane understanding of life and his rehabilitation of the Jewish-Christian understanding of life as created, and hence as something definite.